Pengaruh Pendekatan Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 2 Kota Tidore Kepulauan - Iksan B. Aly; Rafika Fakir (Peneliti.net, 2019)
Contextual approach in the teacher's learning process can apply the Contextual Teaching and Learning (CTL) approach where the school environment can be used by teachers to help students understand concepts that are directly in the environment which makes it easier for teachers to explain the concepts studied with students even though it requires good cooperation between students. teachers and students. SMA Negeri 2 Tidore Islands City is an environmentally oriented school in fact teachers have not taken advantage of the school's vision well, one of which is implementing environment-based learning with the right learning approach where teachers still rely on conventional methods (lectures) that lead to teacher-centered learning processes are only carried out In the classroom, innovation in learning is needed by applying the Contextual Teaching and Learning (CTL) approach. This research is a correlation type with a quasi-experimental approach carried out by SMA Negeri 2 Kota Tidore Kepulauan. The results showed that the use of the Contextual Teaching and Learning (CTL) approach had an effect on student learning outcomes as indicated by the results of Anova analysis at a significance value of 0.010 ≤ 0.05 or sig ≤ 0.05.